Evidence-based clinical practice guideline for chemoprophylaxis, diagnosis, treatments, and discharge management of COVID-19 : evidence evaluation (1) - Ming-Zhen LI; Xia-Mei XU; Shao-Hua HE; Mei-Hua SHEN; Ying-Hui JIN; Li-Ming TAN (Yixue xinzhi zazhi)
Objective To re-evaluate the systematic evaluation of the evidence included in the team's published clinical practice guidelines for COVID-19 drug prevention, diagnosis, treatment, and discharge management.Methods we were electronically searched to collect systematic evaluation/meta-analysis of covid-19 treatment form PubMed, The Cochrane Library, Embase, CNKI and WanFang databases, and important medical journals, preprinted platform and clinical trial registry. The retrieval time was December 1, 2019 to July 8, 2020.AMSTAR 2 tool was used to evaluate the methodological quality of the included system evaluation.Results A total of 6 systematic evaluations/meta-analyses were included, four were drug therapy and two were immunotherapy. The evaluation results of AMSTAR 2 showed that the methodological quality of 1 study was high, 3 were medium, 1 was low, and 1 was extremely low. Methodology deficiencies are mainly reflected in the scheme and registration, analysis methods and funding sources, and so on.Conclusions The methodological quality of the systematic evaluation of COVID-19 treatment is extremely low to high, and some conclusions cannot be determined. High-quality studies with large samples and long-term follow-up are still needed to confirm this.